A Note on An Almost Contanct Metric Manifold withA Type of Semi-symmetric Non-metric Connection - (:unkn) unknown (My University, 2018)
In this paper, we focus on an almost contact metric manifold admitting a type of semi-symmetric nonmetric connection. We find the expression for the curvature tensor of such a manifold. Furhermore, westudy the properties of the curvature tensor and the projective curvature tensor.